Penerapan Model Problem Based Learning (PBL) disertai Artikel Ilmiah untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Kelas X3 SMAN 2 Boyolali Tahun Pelajaran 2012/2013 - Adhi Nurcholis; Suciati Sudarisman; Meti Indrowati (BIO-PEDAGOGI, 2013)
This study was aimed to improve creative thinking ability student in X3 class of SMAN 2 Boyolali through the implementation of problem based learning model accompanied by scientific articles. This research was a classroom action research that divided into several cycles, each cycle includes four stages: planning, action, observation, and reflection. The subject of this research is the students of  X3 class at SMAN 2 Boyolali in academic year of 2012/2013. Data is obtained through the test (esay) and non-test (observation and documentation). Data is analyzed with descriptive analytical techniques and validated by triangulation techniques. The results show that students creative thinking ability is increased in Pre-cycle, Cycle I, Cycle II and Cycle III. There are four aspect in creative thinking ability. The aspect are fluency, flexibility, originality and elaboration. The improvement in fluency aspect increase from 54,55% to 87,27%. Flexibility aspect increase from 37,05% to 84,09%. Originality aspect increase from 48,86% to 86,82%. Elaboration aspect increase from 56,25% to 97,27%. Based on the results of this study the researcher draws a conclusion that the implementation of problem based learning model accompanied by scientifiec articles can improve creative thinking ability student in X3 class at SMAN 2 Boyolali. Key Words: Problem Based Learning, Scientific articles, creative thinking.